2006
DOI: 10.1002/neu.20225
|View full text |Cite
|
Sign up to set email alerts
|

Pax6-induced alteration of cell fate: Shape changes, expression of neuronal α tubulin, postmitotic phenotype, and cell migration

Abstract: The transcription factor Pax6 plays an important role in the development of the central nervous system. To understand its mechanism of action, we transduced HeLa cells with a Pax6-expressing lentiviral vector. Upon transduction, HeLa cells markedly changed shape and formed neuritelike extensions. Pax6-transduced HeLa cells expressed high levels of neuronal alpha3 tubulin, demonstrating a partial transdifferentiation towards a neuronal phenotype. Neurons are postmitotic cells. Pax6-transduced HeLa cells became … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
23
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 68 publications
4
23
0
Order By: Relevance
“…[19][20][21] Accordingly, we previously observed that ectopic Pax6 expression provoked a postmitotic G 0 /G 1 cell-cycle arrest in HeLa cells. 9 This was however not altered by hRFPL1 RNA interference (data not shown), suggesting that hRFPL1 influence on cell-cycle progression is not sufficient to produce cell-cycle exit and differentiation in Pax6-expressing cells.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…[19][20][21] Accordingly, we previously observed that ectopic Pax6 expression provoked a postmitotic G 0 /G 1 cell-cycle arrest in HeLa cells. 9 This was however not altered by hRFPL1 RNA interference (data not shown), suggesting that hRFPL1 influence on cell-cycle progression is not sufficient to produce cell-cycle exit and differentiation in Pax6-expressing cells.…”
Section: Discussionmentioning
confidence: 88%
“…Given the possible role of hRFPL1 on cell-cycle and in silico prediction of putative p53 binding sites on its promoter, we examined the influence of p53 on hRFPL1 transcriptional regulation. Upon Pax6-elicited hRFPL1 expression and p53 activation in HeLa cells, 4,9 we observed using chromatin immunoprecipitation (ChIP) that p53 interacted in vivo with hRFPL1 promoter (Figure 1a). After blocking p53 activity using either cyclic-Pifithrin-a, an inhibitor of p53 nuclear translocation 10 or a p53 shRNA, 11,12 we observed that Pax6-induced hRFPL1 expression was significantly reduced (Figure 1b).…”
Section: Resultsmentioning
confidence: 96%
“…Electroporation of R-cadherin into Pax6-deficient embryos rescued correct outgrowth of pioneer axons during early brain patterning in the mouse (Andrews and Mastick, 2003). Overexpression of Pax6 in transfected HeLa cells induces changes in cellular shape and migration, prompts massive expression of neuronal atubulin, and establishes a postmitotic phenotype (Cartier et al, 2006). Moreover, it was shown that Pax6 regulates the transcription of cadherin 4 (Liu et al, 2001), L1-CAM (Chalepakis et al, 1994;Meech et al, 1999), NCAM (Holst et al, 1997) and a4integrin (Zaniolo et al, 2004).…”
Section: Introductionmentioning
confidence: 97%
“…Myocytes can be differentiated to osteogenic lineage by transfection of RunX1/Cbfa1 [84]. Recently, HeLa tumor cells were transdifferentiated to neurons by forcing the expression of the Pax-6 transcription factor [85]. In vivo, liver cells can be made to differentiate to pancreatic f cells by codelivery of Neuro-D and β-cellulin using gutless adenovirus and thus treat diabetes in an animal model [86].…”
Section: Transdifferentiationmentioning
confidence: 98%
“…For safety purposes, long-term studies on larger animals are necessary in order to predict whether or not a given therapeutic approach will be efficient and without side effects in humans. [16,[20][21][22] Express BMP-7 and HGF [23,73] Immunogenicity Downregulation of MHC class I and co-receptor molecules siRNA, anti-sense RNA, express CTLA-4 Ig [34,110] Autoimmune disease TNF, pro-inflammatory cytokines Express soluble proinflammatory cytokine receptors [110] Express anti-inflammatory cytokines [110] Control unwanted growth Pro-drug activating enzymes Expressing HSV-tk [5] Direct differentiation to a particular pathway Transcription factors Such as Brachyury, Myo-D, Nurr-1, RunX1/Cbfa-1, Pax-6, Neuro-D and β-cellulin [77][78][79][80][81][82][83][84][85][86] Growth/differentiation factors Such as BMP-2,-4, TGF-β, IGF-1 and GDNF [87][88][89][90][91] BMP: Bone morphogenetic protein; IGF: Insulin growth factor; siRNA: Small interfering RNA; TGF:Transforming growth factor.…”
Section: Future Perspectivementioning
confidence: 99%